For a future sustainable, competitive and greener EU budget: integrating the climate change objectives of the EU - Wijkman, Anders; Núñez Ferrer, Jorge; Egenhofer, Christian; Behrens, Arno (Brussels, 2009)
"In March 2009, CEPS formed a Task Force under the chairmanship of Anders Wijkman, former MEP, Vice Chairman of the Taellberg Foundation and Vice President of the Club of Rome, to examine the impacts of climate change and the extent to which the EU budget can effectively assist in addressing them. Based on the discussions among the Task Force members and independent analysis by the rapporteur, Jorge Núñéz Ferrer, with contributions from Christian Egenhofer and Arno Behrens, this report recommends the fundamental reforms to the EU budget, which are necessary for the EU to achieve its objectives on climate change, along with helping it to lead the global effort to curb greenhouse gas emissions."